Thermos-Solid-Gas Coupling Dynamic Model and Numerical Simulation of Coal Containing Gas. (22nd December 2020) - Fukun, Xiao; Xin, Meng; Lianchong, Li; Jianfeng, Liu; Gang, Liu; Zhijun, Liu; Lei, Xu
Abstract : Based on gas seepage characteristics and the basic thermo-solid-gas coupling theory, the porosity model and the dynamic permeability model of coal body containing gas were derived. Based on the relationship between gas pressure, principal stress and temperature, and gas seepage, the thermo-solid-gas coupling dynamic model was established. Initial values and boundary conditions for the model were determined. Numerical simulations using this model were done to predict the gas flow behavior of a gassy coal sample. By using the thermo-solid-gas coupling model, the gas pressure, temperature, and principal stress influence, the change law of the pressure field, displacement field, stress field, temperature field, and permeability were numerically simulated. Research results show the following: (1) Gas pressure and displacement from the top to the end of the model gradually reduce, and stress from the top to the end gradually increases. The average permeability of the Y Z section of the model tends to decrease with the rise of the gas pressure, and the decrease amplitude slows down from the top of the model to the bottom. (2) When the principal stress and temperature are constant, the permeability decreases first and then flattens with the gas pressure. The permeability increases with the decrease of temperature while the gas pressure and principal stress remain unchanged.